CBX3 Promotes Gastric Cancer Progression and Affects Factors Related to Immunotherapeutic Responses - Lin H (Cancer Management and Research, 2020)
Hexin Lin,1,2,* Jiabian Lian,3,4,* Lu Xia,4,5,* Guoxian Guan,2 Jun You1,4 1Department of Gastrointestinal Surgery, The First Affiliated Hospital of Xiamen University, Xiamen, People’s Republic of China; 2Department of Colorectal Surgery, The First Affiliated Hospital of Fujian Medical University, Fuzhou, People’s Republic of China; 3Department of Laboratory Medicine, Xiamen Key Laboratory of Genetic Testing, The First Affiliated Hospital of Xiamen University, Xiamen, People’s Republic of China; 4School of Clinical Medicine, Fujian Medical University, Fuzhou, People’s Republic of China; 5Laboratory of Cancer Center, The First Affiliated Hospital of Xiamen University, Xiamen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun YouDepartment of Gastrointestinal Surgery, The First Affiliated Hospital of Xiamen University, Teaching Hospital of Fujian Medical University, 55 Zhenhai Road, Xiamen, Fujian 361000, People’s Republic of ChinaTel +86-13906051681Email junyou_fahxm@163.comBackground: Chromobox 3 (CBX3) is a member of the chromobox family proteins, which plays a critical role in tumor progression, but the exact function of CBX3 in gastric cancer remains unknown. The current research mainly investigates the underlying mechanisms and clinical value of CBX3 in gastric cancer.Methods: Gene expression cohorts from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) were analyzed to assess the effect of CBX3 in gastric cancer. CBX3 expression was further determined by immunohistochemistry (IHC). The function of CBX3 on proliferation, migration and the cell cycle was explored via colony-forming, cell cycle and transwell assays, respectively. Moreover, RNA sequencing (RNA-seq) in AGS cells and two cohorts was utilized to explore the specific mechanism of CBX3.Results: CBX3 expression was upregulated in human gastric cancer tissues and the expression level was closely associated with adverse signs. Knockdown of CBX3 in gastric cancer cells significantly inhibited the malignant phenotype. In addition, RNA-seq analysis revealed that CBX3 regulates genes related to the cell cycle, mismatch repair and immune-related pathways. Furthermore, the expression of CBX3 was significantly and inversely related to the abundance of tumor-infiltrating lymphocytes (TILs), PDCD1 and PDCD1LG2 expression and immunotherapy responses. Moreover, CBX3 influences the effectiveness of chemotherapy, thereby impacting the prognosis of gastric cancer patients.Conclusion: CBX3 contributes to gastric cancer progression and is associated with chemotherapy and immunotherapy response. CBX3 may serve as a new diagnostic biomarker and potential target for immunotherapy and chemotherapy in gastric cancer.Keywords: chromobox 3, gastric cancer, tumorigenesis, survival, chemotherapy, immunotherapy